Gamification to educate consumers about cybercrime in South Africa - Maselo, Kehilwe Venacia (University of the Witwatersrand, Johannesburg, 2024)
This study examines the impact of gamification on South African consumers attitudes and understanding of cybercrime. Given the increasing reliance on the Internet activities such as social media, digital banking, and e-commerce, there is a critical need for consumers to adopt basic security measures to protect themselves against threats such as privacy breaches, identity theft, cyberbullying, and exposure to harmful content. However, many individuals lack the necessary knowledge and expertise to ensure their online security. The research explores the challenges associated with enhancing security awareness and assesses the potential of gamification techniques to overcome these obstacles. By integrating game mechanics and elements into online security awareness activities, the study aims to make learning about cybersecurity engaging and enjoyable, leading to better understanding and adoption of safe online practices. The findings indicate that gamification significantly enhances consumer engagement, knowledge retention, and proactive cybersecurity behaviours. Additionally, the research contributes to the theoretical framework of Self-Determination Theory (SDT) and behavioural science by providing empirical evidence that intrinsic motivation, fostered through gamification, enhances learning outcomes and behaviour change in cybercrime education. These insights offer valuable implications for businesses and organisations seeking to improve their cybersecurity training and consumer awareness campaigns. Ultimately, this research highlights gamification’s potential to transform cybersecurity education and to promote a more cyber-aware and proactive consumer base in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cybercrime; gamification; knowledge; attitudes; behavioural change; cybersecurity; SDG-8: Decent work and economic growth